CURRENT ISSUES IN PRESERVATION OF RECREATIONAL PTENTIAL OF KYIV REGION - Poltavets, A. M. (Land Management, Cadastre and Land Monitoring, 2013)
Current situation and usage of recreational lands of the Kyiv region is investigated. Research of ways to preserve and disclose the recreational potential of the region is done.